1994
DOI: 10.1007/bf00192445
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of percutaneous aspiration embolectomy

Abstract: PAE is highly effective in the treatment of embolic occlusions of the lower leg arteries and should be considered as an alternative to Fogarty balloon embolectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…The results of AT have been favorable. Wagner et al (16) reported clinical success in 86% of 90 patients and cumulative primary patency rates of 68% and 58% at one and four years, respectively. Major amputation was unavoidable in 8 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of AT have been favorable. Wagner et al (16) reported clinical success in 86% of 90 patients and cumulative primary patency rates of 68% and 58% at one and four years, respectively. Major amputation was unavoidable in 8 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical maceration [16,20,21] seems to give slightly better results than hydrodynamic approaches [1,3,7,22]. In some studies PTA also showed high success rates in the range of 90-95% [1][2][3][4]24]. However, additional thrombolysis was used in 71% [24] and 22% [4] of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…But, as shown in this survey, overall the complication rate of PAE is low and PAE can be performed successfully in most patients. Wagner et al reported on PAE for the treatment of acute arterial embolic infrainguinal vascular occlusion in 85 patients [5]. Clinical success was achieved in 77 of 90 limbs (86%).…”
Section: Discussionmentioning
confidence: 99%
“…Though the technique is applied for more than 30 years there are limited data on the technical and clinical success rate and the rate of complications for this kind of treatment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%